A communication‐less distributed frequency restoration and economical active power control scheme for islanded AC microgrids. (8th November 2021) - Li, Zhiyong; Chen, Gang
Abstract: In this article, a novel distributed cooperative control scheme is presented to restore the microgrid frequency to the nominal value and achieve economical active power sharing. Based on hierarchical control structure, a distributed event‐triggered economic dispatch algorithm is designed to calculate optimal active power reference, and a decentralized frequency controller is developed to restore the microgrid frequency and track the optimal active power reference. The presented scheme is globally distributed for tertiary power optimization and locally decentralized for secondary frequency control. By employing event‐triggered communication mechanism and decentralized secondary frequency control, the communication burden can be significantly reduced. Furthermore, exponential convergence rate of the presented scheme is rigorously proved by Lyapunov approach. Finally, several simulation examples are provided to illustrate the effectiveness of the presented scheme.